Pengembangan Bahan Ajar Modul PPKn Kelas 1 Sekolah Dasar - Lestari, Risda; Setiawati, Rany; Maryanah, Leni; Latip, Asep Ediana (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
This research aims to create a product in the form of a civic education module for learning civic education in the first year of primary school on the material for recognizing the symbols and precepts of Pancasila. This study uses the 4D (Define, Design, Develop and Disseminate) research model, which is a type of research and development (R&D). Three specialists were involved in the study: materials experts, design experts and linguists. In this research, the data collection tool was a questionnaire with an evaluation on a Likert scale. Aiken's V formula was used to analyze the data.. From the calculation results, the following research results were obtained: (1) The average value of the validity test in terms of overall material is 0.892857 with valid status. (2) The average value of the validity test in terms of overall design is 0.964286 with valid status. (3) The average value of the validity test in terms of language as a whole is 0.714286 with valid status. Thus, the Civics module in learning Civics grade 1 elementary school material recognizing the symbols and precepts of Pancasila has good validity and is suitable for use.